2023
DOI: 10.5194/egusphere-2023-2199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol hygroscopicity over the South-East Atlantic Ocean during the biomass burning season: Part I – From the perspective of scattering enhancement

Lu Zhang,
Michal Segal-Rozenhaimer,
Haochi Che
et al.

Abstract: Abstract. Aerosol hygroscopicity plays a vital role in aerosol radiative forcing. One key parameter describing hygroscopicity is the scattering enhancement factor, f (RH), defined as the ratio of the scattering coefficient at humidified relative humidity (RH) to its dry value. Here, we utilize the f (80 %) from ORACLES 2016 and 2018 airborne measurements to investigate the hygroscopicity of aerosols, its vertical distribution, its relationship with chemical composition, and its sensitivity to organic aerosol (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…This good linear relationship between κOA and ALWCOA/ALWC reveals the significant impact of OA hygroscopicity on ALWC over the SEA region during BB episode. The similar PDF distribution of κOA in both campaigns (Zhang et al, 2023) also explains the similar ALWCOA contribution (Fig. 2).…”
Section: Alwc Under Varioussupporting
confidence: 71%
See 3 more Smart Citations
“…This good linear relationship between κOA and ALWCOA/ALWC reveals the significant impact of OA hygroscopicity on ALWC over the SEA region during BB episode. The similar PDF distribution of κOA in both campaigns (Zhang et al, 2023) also explains the similar ALWCOA contribution (Fig. 2).…”
Section: Alwc Under Varioussupporting
confidence: 71%
“…It can be considered as the scattering coefficient weighted average κ (Kuang et al, 2021). The detailed procedure of κf(RH) retrieval can be found in Zhang et al (2023). In Section 3.3 of Kuang et al (2020b), the authors meticulously demonstrated that κf(RH) can accurately represent the κchem of PM1 (particulate matter with an aerodynamic diameter less than 1 μm).…”
Section: Calculation Of Alwcmentioning
confidence: 99%
See 2 more Smart Citations